Snap-N-Send: A valid and reliable method for assessing the energy intake of elite adolescent athletes - Costello, N.; Deighton, K.; Dyson, J.; Mckenna, J.; Jones, B. (European Journal of Sport Science, 2017)
To ensure that elite adolescent athletes meet their unique training, growth and maturation demands, it is imperative to have access to valid measures of energy intake. Contemporary methods demand close attention-to-detail, meaning that athletes often do not fully adhere to real-time protocols. This study represents the first investigation of a real-time dietary assessment designed using a comprehensive behaviour change framework (COM-B). In a crossover design, 12 elite adolescent male rugby players recorded their energy intake via an estimated food diary (est-FD) and photography-based mobile assessment (`Snap-n-Send`), combined with a 24-h dietary recall interview. Two 4-day assessment periods were divided into three separate recording environments: 96 h free-living and researcher-observed; 72 h free-living and 10 h researcher-observed. Assessment periods were one month apart. All foods and beverages were provided and weighed by the research team to quantify actual intakes. `Snap-n-Send` reported a small mean bias for under-reporting across 96 h (-0.75 MJ/day; 95% confidence interval [CI] for bias = -5.7% to -2.2%, p < .001), 72 h (-0.76 MJ/day; 95% CI for bias = -5.6% to -2.1%, p = .004) and 10 h (-0.72 MJ/day; 95% CI for bias = -8.1% to -0.1%; p = .067) environments. The est-FD reported a moderate mean bias for under-reporting across 96 h (-2.89 MJ/day; 95% CI for bias = -17.9% to -10.2%; p < .001), 72 h (-2.88 MJ/day; 95% CI for bias = -17.9% to -10.1%; p < .001) and 10 h (-2.52 MJ/day;-26.1% to -5.3%; p = .023) environments. Results evidence the ability of `Snap-n-Send` to accurately assess the diet of elite adolescent athletes, signalling the exciting promise of this comprehensive and theoretical behavioural approach within valid dietary assessment.